2019
DOI: 10.1111/trf.15559
|View full text |Cite
|
Sign up to set email alerts
|

Platelet in vitro assays: their correspondence with their in vivo hemostatic potential

Abstract: Developments during the past few years have resulted in multiple kinds of platelet products for transfusion. This involves different collection methods, containers, preservative solutions, modifications of storage temperatures and durations, and additional treatments such as pathogen reduction. Much experience has been obtained testing these processes in vitro to seek indications of in vivo effectiveness. Availability of an in vitro method that correlated with in vivo effectiveness would be extremely valuable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…Tests to evaluate the in vitro quality of stored platelets fall in two major groups: (a) indirect parameters of platelet quality (platelet count, metabolism, structure, presence of receptors or activation markers);or (b) direct measurements of adhesive, aggregating, and procoagulant activities of platelets. 25 Metabolic changes in PCs stored for 5 days are characterized by reduction in glucose levels, augmented lactate production, and pH lowering, indicating enhanced anaerobic metabolism. These metabolic changes are associated with alteration of platelet morphology, reductions in glycoproteins, enhanced expression of platelet activation‐ and apoptotic markers, and reduced functional responses.…”
Section: In Vitro Quality Of Platelet Concentratesmentioning
confidence: 99%
“…Tests to evaluate the in vitro quality of stored platelets fall in two major groups: (a) indirect parameters of platelet quality (platelet count, metabolism, structure, presence of receptors or activation markers);or (b) direct measurements of adhesive, aggregating, and procoagulant activities of platelets. 25 Metabolic changes in PCs stored for 5 days are characterized by reduction in glucose levels, augmented lactate production, and pH lowering, indicating enhanced anaerobic metabolism. These metabolic changes are associated with alteration of platelet morphology, reductions in glycoproteins, enhanced expression of platelet activation‐ and apoptotic markers, and reduced functional responses.…”
Section: In Vitro Quality Of Platelet Concentratesmentioning
confidence: 99%
“…4). Various in vitro measures include flow cytometry analysis of the CD42b and CD62P expressions, PAC-1 and Annexin V binding, as well as aggregation assays, clot retraction assays and electron microscopy observations [130,131]. The high level of CD42b expression and low levels of CD62P expression and Annexin V binding at steady state indicate good quality.…”
Section: General Overview and In Vitro Studiesmentioning
confidence: 99%
“…Indeed, several studies characterizing the function in vitro of cold-stored platelets in WB [10,11] and of freeze-dried platelets [12] were published recently; furthermore, an elegant study also demonstrated increased thrombin generation in human autologous transfusions of cold-stored versus room temperature platelets [13]. Additionally, using these approaches, numerous in vitro studies suggest that platelet function deteriorates during storage [14][15][16].…”
Section: Introductionmentioning
confidence: 99%